The Influence of Posterior Cruciate Ligament Resection on Tibiofemoral Joint Gap in Varus Osteoarthritic Knees - Oshima, Yasushi; Majima, Tokifumi; Iizawa, Norishige; Hoshikawa, Naoya; Takahashi, Kenji; Takai, Shinro (The Journal of Knee Surgery, 2020)
Posterior cruciate ligament (PCL) resection during posterior-stabilized total knee arthroplasty (PS-TKA) has been reported to preferentially increase the tibiofemoral joint gap in flexion compared with extension. However, previous assessments of the joint gaps have been performed after bone resection and medial soft tissue release. Thus, these procedural steps may have the potential to influence soft tissue balance. In native knees, soft tissue laxity is generally greater in the lateral compartment than in the medial compartment both with the knee in extension and in flexion. Some surgeons may retain this natural soft tissue balance with less aggressive medial release during TKA. We performed this study to evaluate the impact of the PCL resection on the extension and flexion gaps in the absence of bone resection or medial soft tissue release. Tibiofemoral joint gaps for 41 patients (10 males and 31 females) in full extension and at 90 degrees of flexion both before and after the resections of both the anterior cruciate ligament (ACL) and PCL were assessed using a ligament tensioner device. The statistical analyze was performed using the Mann–Whitney U test. The results showed that medial gap in extension and flexion were 6.7 ± 1.0 and 7.3 ± 0.9 mm, and lateral gap in extension and flexion were 7.6 ± 1.1 and 8.4 ± 1.6 mm, respectively. Thus, physiological tibiofemoral gaps just after knee arthrotomy were trapezoidal and asymmetric shape with the significantly wider gaps in lateral and flexion, compared with the medial and extension, respectively (p < 0.05). However, the increases of the gaps with the ACL and PCL resections were less than 1 mm under the existence of medial soft tissues. As the medial collateral ligament is the primary restraint for the valgus instability, it was also considered to prevent the increase of the flexion gap although the PCL—which is the secondary restraint for the valgus instability—was resected. This finding is critically important for orthopedic surgeons applying PS-TKA implants, particularly for preserving soft tissues to achieve natural knee kinematics postoperatively.
Keywords: total knee arthroplasty; tibiofemoral joint gap; ligament tensioner; posterior cruciate ligament resection; osteoarthritis of the knee